Research on the influence of patient cost-sharing on medical expenses and health outcomes: Taking patients with heart failure as an example - Zhang, Huyang; Ning, Ke; Wang, Jinxi; Fang, Hai (Frontiers in Public Health, 2023)
Objective: The objective of this study is to assess the impact of the changes in patient cost-sharing on the medical expenses and health outcomes of patients with heart failure in China. Methods: The claim data of patients diagnosed with heart failure enrolled in the Urban Employees’ Basic Medical Insurance (UEBMI) in Zhejiang province, China was utilized, covering the period from January 1st, 2013 to December 31st, 2017. The impact of the policy change was estimated through the use of the difference-in-differences method and the event study method. Results: A total of 6766 patients and their electronic health insurance claim data were included in the baseline year of 2013. Following the change in the UEBMI reimbursement policies (policy change), a notable decrease was observed in the patient cost-sharing ratios, particularly in the copayment ratio within the policy. However, it did not result in a reduction of the out-of-pocket ratio, which remains a primary concern among patients. An increase was observed in annual outpatient medical expenses, while annual inpatient medical expenses decreased, leading to a higher annual medical expense in the treatment group in comparison to the control group. The effect of the UEBMI reimbursement policy change on health outcomes showed a reduction in the rehospitalization rate within 90 days, however, no significant impact was seen on the rehospitalization rate within 30 days. Conclusion: The impact of the policy change on medical expenses and health outcomes was found to be modest. To effectively address the financial burden on patients, it is crucial for policymakers to adopt a comprehensive approach that considers all aspects of medical insurance policies, including reimbursement policies.